Examining SERVQUAL Dimensions and Patient Satisfaction Using PLS-SEM: Evidence From an Indonesian Public Health Center - Vira Geraldine Arliska; Mohammad Agung Saryatmo (DINASTI RESEARCH, 2026)
Primary healthcare centers in Indonesia face persistent service quality challenges, yet empirical studies employing structural modeling in resource-constrained settings remain scarce. This study analyzes the effect of the five SERVQUAL dimensions—tangibles, reliability, responsiveness, assurance, and empathy—on patient satisfaction at Keboan Ngusikan Public Health Center, Jombang Regency, East Java. Using a quantitative cross-sectional design, 300 outpatients were selected via purposive sampling and surveyed with a validated Likert-scale instrument. Partial Least Squares–Structural Equation Modeling (PLS-SEM) was applied for analysis. All five dimensions exerted a positive and statistically significant effect on patient satisfaction. Responsiveness emerged as the most influential predictor, followed by tangibles, assurance, empathy, and reliability. The model demonstrated strong explanatory power (R² = 0.712), explaining 71.2% of variance in patient satisfaction. These findings extend Service Quality Theory to a primary care context with staffing constraints, offering actionable implications for healthcare managers and policymakers seeking to improve service delivery at community health centers across Indonesia.